AKUNTABILITAS PERTANGGUNGJAWABAN ALOKASI DANA DESA TAHUN ANGGARAN 2013 DI DESA BADAK BARU KECAMATAN MUARA BADAK KABUPATEN KUTAI KARTANEGARA - -, Alvianty - (EKONOMIA, 2014)
This study aims to determine the allocation of village funds accountability report (budget realization report for fiscal year 2013) in accordance with the Regulation of the Minister of the Interior in 2007 that the explanations Number 37 the descriptions contained in the Regulations of Regents Number 72 of 2008 on the Financial Management Guidelines Village.The formulation of the research problem is the allocation of village funds accountability report for fiscal year 2013 in the village Badak Baru of Muara Badak sub-district Kutai Kertanegara regency has according to Interior Minister of Home Affairs Regulation Number 37 of 2007.Basic theory in this study is the accounting to focused on accountability of public sector accountability and use of village funds allocation proportion of the allocation of village funds for fiscal year 2013 in the village of Badak Baru. The hypothesis of this study is the allocation of village funds accountability report for fiscal year 2013 in the village of Badak Baru, Muara Badak Kutai Kertanegara not in accordance yet with the Regulation of the Minister of Home Affairs Number 37 Year 2007The analytical tool used in this study is the Minister of Home Affairs Number 37 Year 2007 on Guidelines for Management of Rural Finance in Article 22., And report realization of the village budget allocations for fiscal year 2013.Based on the analysis and discussion it was concluded that the allocation of village funds accountability report for fiscal year 2013 is not in accordance with the Regulation of the Minister of Home Affairs No. 37 of 2007 in the present budget realization report occur the following matters:Â Findings support the hypothesis received reports the percentage proportion of the budget allocation of village funds are supposed to use 30% (thirty percent)for operational expenditures and government officials in the village of realization becomes 30.72% (Thirty-two point seventy-two percent)And the use of the budget that should be 70% (seventy percent) of the cost of community empowerment in the realization becomes 65.15% (Sixty-five point fifteen percent), causes it to weak absorption in budget planning and budget, there are still budget SILPA (Surplus budget calculations) can not be realized in fiscal year 2013 amounted to 4:14% (Four Koma Fourteen percent)